ISSUES OF ENSURING ACTIVE PARTICIPATION OF CIVIL SOCIETY INSTITUTIONS IN ELECTORAL PROCESSES AND FURTHER IMPROVEMENT OF THEIR ORGANISATIONAL AND LEGAL FOUNDATIONS (Academia Science Repository, 2023)
The role of genuine, fair and democratic elections in the implementation of democratic reforms is unparalleled. Therefore, the power of the people is inconceivable without democratic elections. The adoption of the Election Code of the Republic of Uzbekistan serves as an important legal basis for the construction of a new Uzbekistan, as well as for the implementation of our citizens’ right to vote, the establishment of the rule of law and the development of civil society.